Outrage: the rise of religious offence in contemporary South Asia - Rollier, Paul; Frøystad, Kathinka; Ruud, Arild Engelsen (UCL Press, 2019)
Whether spurred by religious images or academic history books, hardly a day goes by in South Asia without an incident or court case occurring as a result of hurt religious feelings. The sharp rise in blasphemy accusations over the past few decades calls for an investigation into why offence politics has become so prono
Keywords: Aufsatzsammlung; Gotteslästerung; Religionsfreiheit; Religionsdelikt; Südasien